Charles Cormier talks about building houses and boats - Tuton, Hazel (1983)
Charles Cormier parle de la construction, des moulins, et des matériaux necessaires pour construire une maison. Il parle des bateaux et leur construction. Il parle des divisions de terre et des héritages des lots de terre. -- Charles Cormier speaks about construction, mills and what building materials are needed to build a house. He also shares his knowledge of boat building and talks about land division and inheritance. Suite du C7257 -- Continues from C7257